Editorial Comments/ Redaksionele Kommentaar - A D Stuart (AOSIS, 2003)
A theoretical ideal for the sciences as propagated by the Ancient Greeks, inter alia Aristotle, stated as basis Knowledge for the sake of Knowledge. Opsomming 'n Teoretiese ideaal vir wetenskap is reeds deur die Antieke Grieke, onder andere Artistoleles, gepropageer, waar Kennis ter wille van Kennis as grondslag gestel is. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.